Feasibility, safety and efficacy of two-stage hepatectomy for bilobar liver metastases of colorectal cancer: a LiverMetSurvey analysis. Issue 5 (May 2017) - Regimbeau, Jean Marc; Cosse, Cyril; Kaiser, Gernot; Hubert, Catherine; Laurent, Christophe; Lapointe, Real; Isoniemi, Helen; Adam, Rene
Abstract: Background: The combination of liver resection and chemotherapy has become the standard of care for colorectal liver metastases (LM). The objective of the present study was to evaluate the impact of two-stage hepatectomy (TSH) on the long-term survival of patients with bilobar LM. Methods: We included adult (over-18) patients from the LiverMetSurvey registry with confirmed multiple colorectal LM and having undergone either one-stage hepatectomy or TSH with curative intent. The "TSH (2/2)" group (n = 625) comprised patients having completed both stages of TSH; the "TSH (1/2)" group (n = 244) comprised patients having undergone only the first stage of TSH; the "hepatectomy" group. The primary outcome criterion was the overall survival (OS). The secondary outcomes were the morbidity and mortality rates. Results: The 30- and 90-day mortality rates were respectively 3.8% and 9.3% in the TSH (2/2) group, 9.4% and 16.4% in the TSH (1/2) group, and 5.4% and 9.1% in the "hepatectomy" group. The three-year OS rate was 45% in the TSH (2/2) group, 30% in the TSH (1/2) group and 50.7% in the hepatectomy group. Conclusion: The LiverMetSurvey registry's data indicate that TSH is associated with rather good long-term survival and acceptable morbidity and mortality rates.